The next Christians : the good news about the end of Christian America - Lyons, Gabe, 1975- (New York : Doubleday Religion, 2010)
Lyons carefully observes the end of Christian America's dominance and offers a compelling vision for how followers of Jesus can recover their core identity while faithfully navigating our current cultural milieu.
Fading reality -- New normal -- Parody of ourselves -- Relearning restoration -- Provoked, not offended -- Creators, not critics -- Called, not employed -- Grounded, not distrated -- In community, not alone -- Countercultural, not "relevant" -- Next big shift.
Includes bibliographical references (p. [209]-224) and index.
Keywords: Christianity -- United States -- 21st century; United States -- Church history -- 21st century; Christianity -- United States; United States -- Church history